The feasibility and accuracy of ultrasound assessment in the labor room. (18th October 2019) - Usman, S.; Wilkinson, M.; Barton, H.; Lees, C. C.
Abstract: Objective: Vaginal examination is widely used to assess the progress of labor; however, it is subjective and poorly reproducible. We aim to assess the feasibility and accuracy of transabdominal and transperineal ultrasound compared to vaginal examination in the assessment of labor and its progress. Methods: Women were recruited as they presented for assessment of labor to a tertiary inner city maternity service. Paired vaginal and ultrasound assessments were performed in 192 women at 24–42 weeks. Fetal head position was assessed by transabdominal ultrasound defined in relation to the occiput position transformed to a 12-hour clock face; fetal head station defined as head-perineum distance by transperineal ultrasound; cervical dilatation by anterior to posterior cervical rim measurement and caput succedaneum by skin-skull distance on transperineal ultrasound. Results: Fetal head position was recorded in 99.7% (298/299) of US and 51.5% (154/299) on vaginal examination ( p < .0001 1 ). Bland–Altman analysis showed 95% limits of agreement, −5.31 to 4.84 clock hours. Head station was recorded in 96.3% (308/320) on vaginal examination (VE) and 95.9% (307/320) on US ( p = .79 1 ). Head station and head perineum distance were negatively correlated (Spearman's r = −.57, p < .0001). 54.4% (178/327) of cervical dilatation measurements were determined using US and 100% on VE/speculum ( p < .0001). Bland–Altman analysis showed 95% limits of agreement −2.51–2.16 cm. The presence of caput could be assessed in 98.4% (315/320) of US and was commented in 95.3% (305/320) of VEs, with agreement for the presence of caput of 76% ( p < .05). Fetuses with caput greater than 10 mm had significantly lower head station ( p < .0001). Conclusions: We describe comprehensive ultrasound assessments in the labor room that could be translated to the assessment of women in labor. Fetal head position is unreliably determined by vaginal examination and agrees poorly with US. Head perineum distance has a moderate correlation with fetal head station in relation to the ischial spines based on vaginal examination. Cervical dilatation is not reliably assessed by ultrasound except at dilatations of less than 4 cm. Caput is readily quantifiable by ultrasound and its presence is associated with lower fetal head station. Transabdominal and transperineal ultrasound is feasible in the labor room with an accuracy that is generally greater than vaginal examinations.